2021
DOI: 10.1136/tobaccocontrol-2021-056522
|View full text |Cite
|
Sign up to set email alerts
|

Primary care-based smoking cessation treatment and subsequent healthcare service utilisation: a matched cohort study of smokers using linked administrative healthcare data

Abstract: BackgroundNo research has assessed the individual-level impact of smoking cessation treatment delivered within a general primary care patient population on multiple forms of subsequent healthcare service use.ObjectiveWe aimed to compare the rate of outpatient visits, emergency department (ED) visits and hospitalisations during a 5-year follow-up period among smokers who had and had not accessed a smoking cessation treatment programme.MethodsThe study was a retrospective matched cohort study using linked demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…In sensitivity analysis, the inclusion of sick quitters almost was not possible because we included quitters (past smokers) who had already stopped smoking before baseline. This trend aligns with the well-documented phenomenon of escalated medical use and associated expenses among those who have just quit …”
Section: Discussionsupporting
confidence: 78%
“…In sensitivity analysis, the inclusion of sick quitters almost was not possible because we included quitters (past smokers) who had already stopped smoking before baseline. This trend aligns with the well-documented phenomenon of escalated medical use and associated expenses among those who have just quit …”
Section: Discussionsupporting
confidence: 78%
“…In these perspectives, a few studies suggested a decrease in some healthcare costs in the year postsmoking cessation treatment, but these findings resulted from the limited study design and target population, such as the comparison of smokers with or without inpatient tobacco dependence treatment during the hospitalization or the comparison of varenicline versus NRT users without comparison to the non-treated group 20,21 . While some previous studies, including two recently published studies from Ontario, Canada, based on the longitudinal followup design using real-world measurement of the healthcare cost linked with administrative healthcare data, showed an increase in or relatively higher medical utilization and cost among the smoking cessation service users [22][23][24][25] . One study reported higher total healthcare costs in the treatment cohort pre-and post-treatment periods 24 , and another study identified a significantly greater rate of outpatient visits, emergency department visits and hospitalizations among patients who enrolled in smoking cessation treatment offered through primary care clinics over a 5-year follow-up period 25 .…”
Section: Discussionmentioning
confidence: 93%
“…The propensity score was calculated using the method of multivariate logistic regression, and the following covariates were included in the multivariate logistic regression model as factors affecting an individual who participated in the HBVIDV program: age, gender, education level, employment condition, economic level, self-rated socioeconomic status, living area, multimorbidity, and self-rated health condition. The missing data of categorical covariates were coded as the "Missing" category and were included in the propensity score matching analysis [20]. After the propensity score was estimated, a 1:1 match without replacement was performed using nearest neighbor matching with a 0.2 SD caliper width.…”
Section: Discussionmentioning
confidence: 99%